Has the shortage of fludarabine altered the current paradigm of lymphodepletion in favor of bendamustine? - Filioglou, Dimitrios; Husnain, Muhammad; Khurana, Sharad; Simpson, Richard J.; Katsanis, Emmanuel (Frontiers in Immunology, 2023)
The most common lymphodepletion regimen used prior to infusion of chimeric antigen receptor-T cells (CAR-T) is cyclophosphamide (CY) in combination with fludarabine (Flu) (CY-FLU). While cyclophosphamide (CY) possesses lymphotoxic effects, it concurrently preserves regulatory T cell activity, potentially affecting the efficacy of CAR-T cells. Moreover, the use of fludarabine (FLU) has been linked to neurotoxicity, which could complicate the early detection of immune effector cell-associated neurotoxicity syndrome (ICANS) observed in CAR-T cell therapy. Given the ongoing shortage of FLU, alternative lymphodepleting agents have become necessary. To date, only a limited number of studies have directly compared different lymphodepleting regimens, and most of these comparisons have been retrospective in nature. Herein, we review the current literature on lymphodepletion preceding CAR-T cell therapies for lymphoid hematologic malignancies, with a specific focus on the use of bendamustine (BEN). Recent evidence suggests that administering BEN before CAR-T cell infusion yields comparable efficacy, possibly with a more favorable toxicity profile when compared to CY-FLU. This warrants further investigation through randomized prospective studies.